Rural Electrification Using Shield Wire Schemes - Gbedey, Franklin K.; Vilar Ferrenbach, David; Lemondzhava, Tatia (World Bank, Washington, DC, 2017)
Shield wire systems running along existing high-voltage transmission lines can supply household electricity to communities located within 20 km of the high-voltage corridor. At a fraction of the cost of new substations or independent medium-voltage lines, shield wire systems are an attractive option for rural electrification, particularly in remote and sparsely populated areas that are costly to connect to the grid. Systems have operated successfully in Sub- Saharan Africa and elsewhere for more than a quarter-century. A new manual assists engineers in designing and building shield wire systems.